Da mesquita à catedral, percurso por um lugar central em Lisboa - Jacinta Bugalhão (Medievalista, 2025)
This paper seeks to present, in a very synthetic way, the historical, archaeological and urban data that contribute to the hypothesis: the Aljama mosque of al-Ushbuna was in the place where the Lisbon Cathedral is located today. The construction of Christian church represents a classic example of the reversibility of urban sacred spaces, between the Gharb al-Andalus and the medieval kingdom of Portugal. Under the cloister and the embankment that provides the infrastructure, to the east of the Cathedral, ruins of a monumental building from the Islamic period are preserved which is interpreted as the aljama mosque complex of al-Ushbuna.